Electrochemical diffusimetry of fuel cell gas diffusion layers - Kramer, Denis; Freunberger, Stefan Alexander; Flückiger, Reto; Schneider, Ingo A.; Wokaun, Alexander; Büchi, Felix N.; Scherer, Günther G. (Journal of Electroanalytical Chemistry)
The gas diffusion layers (GDLs) of a membrane electrode assembly (MEA) serve as link between flow field and porous electrode within a polymer electrolyte fuel cell. Beside ensuring sufficient electrical and thermal contact between the whole electrode area and the flow field, these typically 200–400 μm thick porous structures enable the access of educts to the electrode area which would be occluded by the flow field lands if the flow field is directly attached to the electrode. Hence, the characterisation of properties pertaining to mass transport of educts and products through these structures is indispensable whilst examining the contribution of the GDLs to the overall electrochemical characteristics of a MEA. A fast and cost effective method to measure the effective diffusivity of a GDL is presented. Electrochemical impedance spectroscopy is applied to measure the effective ionic conductivity of an electrolyte-soaked GDL. Taking advantage of the analogy between Ficks and Ohms law, this provides a measure for the effective diffusivity. The method is described in detail, including experimental as well as theoretical aspects, and selected results, highlighting the anisotropy and dependence on the degree of compression, are shown. Moreover, a two-dimensional model consisting of regularly spaced ellipses is developed to represent the porous structure of the GDL, and by using conformal maps, the agreement between this model and experiment with respect to the sensitivity of the effective diffusivity towards compression is shown.

Experimental investigation of the propagation of local current density variations to adjacent cells in PEFC stacks - Santis, Marco; Freunberger, Stefan Alexander; Papra, Matthias; Büchi, Felix N. (3rd International Conference on Fuel Cell Science, Engineering and Technology)
The propagation of single cell performance losses to adjacent cells in a polymer electrolyte fuel cell stack is studied by means of local current density measurements in a two cell stack. In this stack, the working conditions of adjacent cells can be controlled independently in order to deliberately change the performance of one cell (inducing cell) and study the coupling effects to the adjacent cell (response cell), while keeping the working conditions of the later one unchanged. The experiments have shown that changes in the current density distribution caused by lowering of the air stoichiometry in the inducing cell cause changes in the current density distribution of the response cell in the order of 60% of the change of the inducing cell, even when the air stoichiometry of the response cell is kept constant. The losses in cell voltage of the inducing cell cause losses in cell voltage of the response cell in a magnitude between 30 and 50%.

How to solve consensus in the smallest window of synchrony - Alistarh, Dan-Adrian; Gilbert, Seth; Guerraoui, Rachid; Travers, Corentin
This paper addresses the following question: what is the minimum-sized synchronous window needed to solve consensus in an otherwise asynchronous system? In answer to this question, we present the first optimally-resilient algorithm ASAP that solves consensus as soon as possible in an eventually synchronous system, i.e., a system that from some time GST onwards, delivers messages in a timely fashion. ASAP guarantees that, in an execution with at most f failures, every process decides no later than round GST + f + 2, which is optimal.

Estimation of 2Nes From Temporal Allele Frequency Data - Jonathan Bollback; York, Thomas L; Nielsen, Rasmus (Genetics)
We develop a new method for estimating effective population sizes, Ne, and selection coefficients, s, from time-series data of allele frequencies sampled from a single diallelic locus. The method is based on calculating transition probabilities, using a numerical solution of the diffusion process, and assuming independent binomial sampling from this diffusion process at each time point. We apply the method in two example applications. First, we estimate selection coefficients acting on the CCR5-Δ32 mutation on the basis of published samples of contemporary and ancient human DNA. We show that the data are compatible with the assumption of s = 0, although moderate amounts of selection acting on this mutation cannot be excluded. In our second example, we estimate the selection coefficient acting on a mutation segregating in an experimental phage population. We show that the selection coefficient acting on this mutation is ~0.43.

Assigning trust to Wikipedia content - Adler, B Thomas; Krishnendu Chatterjee; de Alfaro, Luca; Faella, Marco; Pye, Ian; Raman, Vishwanath
The Wikipedia is a collaborative encyclopedia: anyone can contribute to its articles simply by clicking on an "edit" button. The open nature of the Wikipedia has been key to its success, but has also created a challenge: how can readers develop an informed opinion on its reliability? We propose a system that computes quantitative values of trust for the text in Wikipedia articles; these trust values provide an indication of text reliability. The system uses as input the revision history of each article, as well as information about the reputation of the contributing authors, as provided by a reputation system. The trust of a word in an article is computed on the basis of the reputation of the original author of the word, as well as the reputation of all authors who edited text near the word. The algorithm computes word trust values that vary smoothly across the text; the trust values can be visualized using varying text-background colors. The algorithm ensures that all changes to an article's text are reflected in the trust values, preventing surreptitious content changes. We have implemented the proposed system, and we have used it to compute and display the trust of the text of thousands of articles of the English Wikipedia. To validate our trust-computation algorithms, we show that text labeled as low-trust has a significantly higher probability of being edited in the future than text labeled as high-trust.

Robust content-driven reputation - Krishnendu Chatterjee; de Alfaro, Luca; Pye, Ian
In content-driven reputation systems for collaborative content, users gain or lose reputation according to how their contributions fare: authors of long-lived contributions gain reputation, while authors of reverted contributions lose reputation. Existing content-driven systems are prone to Sybil attacks, in which multiple identities, controlled by the same person, perform coordinated actions to increase their reputation. We show that content-driven reputation systems can be made resistant to such attacks by taking advantage of thefact that the reputation increments and decrements depend on content modifications, which are visible to all. We present an algorithm for content-driven reputation that prevents a set of identities from increasing their maximum reputation without doing any useful work. Here, work is considered useful if it causes content to evolve in a direction that is consistent with the actions of high-reputation users. We argue that the content modifications that require no effort, such as the insertion or deletion of arbitrary text, are invariably non-useful. We prove a truthfullness result for the resulting system, stating that users who wish to perform a contribution do not gain by employing complex contribution schemes, compared to simply performing the contribution at once. In particular, splitting the contribution in multiple portions, or employing the coordinated actions of multiple identities, do not yield additional reputation. Taken together, these results indicate that content-driven systems can be made robust with respect to Sybil attacks. Copyright 2008 ACM.

Algorithms for game metrics - Chatterjee, Krishnendu; De Alfaro, Luca; Majumdar, Ritankar; Raman, Vishwanath
Simulation and bisimulation metrics for stochastic systems provide a quantitative gen- eralization of the classical simulation and bisimulation relations. These metrics capture the similarity of states with respect to quantitative specifications written in the quantitative μ-calculus and related probabilistic logics. We present algorithms for computing the metrics on Markov decision processes (MDPs), turn- based stochastic games, and concurrent games. For turn-based games and MDPs, we provide a polynomial-time algorithm based on linear programming for the computation of the one-step metric distance between states. The algorithm improves on the previously known exponential-time algo- rithm based on a reduction to the theory of reals. We then present PSPACE algorithms for both the decision problem and the problem of approximating the metric distance between two states, matching the best known bound for Markov chains. For the bisimulation kernel of the metric, which corresponds to probabilistic bisimulation, our algorithm works in time O(n4) for both turn-based games and MDPs; improving the previously best known O(n9 · log(n)) time algorithm for MDPs. For a concurrent game G, we show that computing the exact distance between states is at least as hard as computing the value of concurrent reachability games and the square-root-sum problem in computational geometry. We show that checking whether the metric distance is bounded by a rational r, can be accomplished via a reduction to the theory of real closed fields, involving a formula with three quantifier alternations, yielding O(|G|O(|G|5)) time complexity, improving the previously known reduction with O(|G|O(|G|7)) time complexity. These algorithms can be iterated to approximate the metrics using binary search.

Theta phase-specific codes for two-dimensional position, trajectory and heading in the hippocampus - Huxter,John R; Senior,Timothy J; Allen, Kevin; Jozsef Csicsvari (Nature Neuroscience)
Temporal coding is a means of representing information by the time, as opposed to the rate, at which neurons fire. Evidence of temporal coding in the hippocampus comes from place cells, whose spike times relative to theta oscillations reflect a rat's position while running along stereotyped trajectories. This arises from the backwards shift in cell firing relative to local theta oscillations (phase precession). Here we demonstrate phase precession during place-field crossings in an open-field foraging task. This produced spike sequences in each theta cycle that disambiguate the rat's trajectory through two-dimensional space and can be used to predict movement direction. Furthermore, position and movement direction were maximally predicted from firing in the early and late portions of the theta cycle, respectively. This represents the first direct evidence of a combined representation of position, trajectory and heading in the hippocampus, organized on a fine temporal scale by theta oscillations.

Reactivation of experience-dependent cell assembly patterns in the hippocampus - Joseph O'Neill; Senior,Timothy J; Allen, Kevin; Huxter,John R; Jozsef Csicsvari (Nature Neuroscience)
The hippocampus is thought to be involved in episodic memory formation by reactivating traces of waking experience during sleep. Indeed, the joint firing of spatially tuned pyramidal cells encoding nearby places recur during sleep. We found that the sleep cofiring of rat CA1 pyramidal cells encoding similar places increased relative to the sleep session before exploration. This cofiring increase depended on the number of times that cells fired together with short latencies ( < 50 ms) during exploration, and was strongest between cells representing the most visited places. This is indicative of a Hebbian learning rule in which changes in firing associations between cells are determined by the number of waking coincident firing events. In contrast, cells encoding different locations reduced their cofiring in proportion to the number of times that they fired independently. Together these data indicate that reactivated patterns are shaped by both positive and negative changes in cofiring, which are determined by recent behavior.

Ivy cells: A population of nitric-oxide-producing, slow-spiking GABAergic neurons and their involvement in hippocampal network activity - Fuentealba,Pablo; Begum,Rahima; Capogna,Marco; Jinno,Shozo; Marton,Laszlo F; Jozsef Csicsvari; Thomson,Alex; Somogyi, Péter; Klausberger,Thomas (Neuron)
In the cerebral cortex, GABAergic interneurons are often regarded as fast-spiking cells. We have identified a type of slow-spiking interneuron that offers distinct contributions to network activity. “Ivy” cells, named after their dense and fine axons innervating mostly basal and oblique pyramidal cell dendrites, are more numerous than the parvalbumin-expressing basket, bistratified, or axo-axonic cells. Ivy cells express nitric oxide synthase, neuropeptide Y, and high levels of GABA(A) receptor alpha 1 subunit; they discharge at a low frequency with wide spikes in vivo, yet are distinctively phase-locked to behaviorally relevant network rhythms including theta, gamma, and ripple oscillations. Paired recordings in vitro showed that Ivy cells receive depressing EPSPs from pyramidal cells, which in turn receive slowly rising and decaying inhibitory input from Ivy cells. In contrast to fast-spiking interneurons operating with millisecond precision, the highly abundant Ivy cells express presynaptically acting neuromodulators and regulate the excitability of pyramidal cell dendrites through slowly rising and decaying GABAergic inputs.

Inhibitory interneurons and network oscillations - Dupret, David; Pleydell-Bouverie, Barty; Jozsef Csicsvari (PNAS)

Gamma oscillatory firing reveals distinct populations of pyramidal cells in the CA1 region of the hippocampus - Senior,Timothy J; Huxter,John R; Allen, Kevin; Joseph O'Neill; Jozsef Csicsvari (Journal of Neuroscience)
Hippocampal place cells that fire together within the same cycle of theta oscillations represent the sequence of positions (movement trajectory) that a rat traverses on a linear track. Furthermore, it has been suggested that the encoding of these and other types of temporal memory sequences is organized by gamma oscillations nested within theta oscillations. Here, we examined whether gamma-related firing of place cells permits such discrete temporal coding. We found that gamma-modulated CA1 pyramidal cells separated into two classes on the basis of gamma firing phases during waking theta periods. These groups also differed in terms of their spike waveforms, firing rates, and burst firing tendency. During gamma oscillations one group's firing became restricted to theta phases associated with the highest gamma power. Consequently, on the linear track, cells in this group often failed to fire early in theta-phase precession (as the rat entered the place field) if gamma oscillations were present. The second group fired throughout the theta cycle during gamma oscillations, and maintained gamma-modulated firing at different stages of theta-phase precession. Our results suggest that the two different pyramidal cell classes may support different types of population codes within a theta cycle: one in which spike sequences representing movement trajectories occur across subsequent gamma cycles nested within each theta cycle, and another in which firing in synchronized gamma discharges without temporal sequences encode a representation of location. We propose that gamma oscillations during theta-phase precession organize the mnemonic recall of population patterns representing places and movement paths.

Disrupted dopamine transmission and the emergence of exaggerated beta oscillations in subthalamic nucleus and cerebral cortex - Mallet,Nicolas; Pogosyan,Alek; Sharott,Andrew; Jozsef Csicsvari; Bolam, John Paul; Brown,Peter; Magill,Peter J (Journal of Neuroscience)
In the subthalamic nucleus (STN) of Parkinson's disease (PD) patients, a pronounced synchronization of oscillatory activity at beta frequencies (15-30 Hz) accompanies movement difficulties. Abnormal beta oscillations and motor symptoms are concomitantly and acutely suppressed by dopaminergic therapies, suggesting that these inappropriate rhythms might also emerge acutely from disrupted dopamine transmission. The neural basis of these abnormal beta oscillations is unclear, and how they might compromise information processing, or how they arise, is unknown. Using a 6-hydroxydopamine-lesioned rodent model of PD, we demonstrate that beta oscillations are inappropriately exaggerated, compared with controls, in a brain-state-dependent manner after chronic dopamine loss. Exaggerated beta oscillations are expressed at the levels of single neurons and small neuronal ensembles, and are focally present and spatially distributed within STN. They are also expressed in synchronous population activities, as evinced by oscillatory local field potentials, in STN and cortex. Excessively synchronized beta oscillations reduce the information coding capacity of STN neuronal ensembles, which may contribute to parkinsonian motor impairment. Acute disruption of dopamine transmission in control animals with antagonists of D-1/D-2 receptors did not exaggerate STN or cortical beta oscillations. Moreover, beta oscillations were not exaggerated until several days after 6-hydroxydopamine injections. Thus, contrary to predictions, abnormally amplified beta oscillations in cortico-STN circuits do not result simply from an acute absence of dopamine receptor stimulation, but are instead delayed sequelae of chronic dopamine depletion. Targeting the plastic processes underlying the delayed emergence of pathological beta oscillations after continuing dopaminergic dysfunction may offer considerable therapeutic promise.

Skeletal structures - Biasotti, Silvia; Attali, Dominique; Boissonnat, Jean-Daniel; Herbert Edelsbrunner; Elber, Gershon; Mortara, Michela; Sanniti di Baja, Gabriella; Spagnuolo, Michela; Tanase, Mirela; Veltkam, Remco (Shape Analysis and Structuring)

Probing E-cadherin endocytosis by morpholino-mediated Rab5 knock-down in zebrafish. - Ulrich, Florian; Heisenberg, Carl-Philipp J (Methods in Molecular Biology)
The controlled internalization of membrane receptors and lipids is crucial for cells to control signaling pathways and interact with their environment. During clathrin-mediated endocytosis, membrane constituents are transported via endocytic vesicles into early endosomes, from which they are further distributed within the cell. The small guanosine triphosphatase (GTPase) Rab5 is both required and sufficient for the formation of these early endosomes and can be used to experimentally address endocytic processes. Recent evidence shows that endocytic turnover of E-cadherin regulates the migration of mesendodermal cells during zebrafish gastrulation by modulating their adhesive interactions with neighboring cells. This in turn leads to effective and synchronized movement within the embryo. In this review, we discuss techniques to manipulate E-cadherin endocytosis by morpholino-mediated knockdown of rab5 during zebrafish gastrulation. We describe the use of antibodies specifically directed against zebrafish E-cadherin to detect its intracellular localization and of in situ hybridization and primary cell culture to reveal patterns of cell migration and adhesion, respectively

Adaptive formation control and bio-inspired optimization of a cluster-based satellite wireless sensor network - Yang, Erfu; Erdogan, Ahmet T; Arslan, Tughrul; Nicholas Barton
In this paper, adaptive formation control and bio-inspired optimization are jointly addressed for a cluster-based satellite wireless sensor network in which there are multiple satellites flying in formation (MSFF) in the presence of unknown disturbances. The full nonlinear dynamics model describing the relative positioning of the MSFF system is used to develop an adaptive formation controller. First, the original nonlinear system is transformed into a linear controllable system with aperturbation term by invoking the input-output feedback linearization technique. Second, by using the integral feedback design scheme, the adaptive formation controller is presented for improving the steady-state performance of the MSFF system in the presence of unknown disturbances. Third, as a currently popular bio-inspired algorithm, PSO (particle swarm optimizer) is employed to minimize the total energy consumption under the required quality of service by jointly optimizing the transmission power and rate for each satellite. Simulation results are provided to demonstrate the effectiveness of the adaptive formation controller and the PSO-based optimization for saving the total communication energy.

Scalability of a novel shifting balance theory-based optimization algorithm: A comparative study on a cluster-based wireless sensor network - Yang, Erfu; Nicholas Barton; Arslan, Tughrul; Erdogan, Ahmet T
Scalability is one of the most important issues for optimization algorithms used in wireless sensor networks (WSNs) since there are often many parameters to be optimized at the same time. In this case it is very hard to ensure that an optimization algorithm can be smoothly scaled up from a low-dimensional optimization problem to the one with a high dimensionality. This paper addresses the scalability issue of a novel optimization algorithm inspired by the Shifting Balance Theory (SBT) of evolution in population genetics. Toward this end, a cluster-based WSN is employed in this paper as a benchmark to perform a comparative study. The total energy consumption is minimized under the required quality of service by jointly optimizing the transmission power and rate for each sensor node. The results obtained by the SBT-based algorithm are compared with the Metropolis algorithm (MA) and currently popular particle swarm optimizer (PSO) to assess the scaling performance of the three algorithms against the same WSN optimization problem.

A model for the evolution of assortative mating - De Cara, Maria A; Nicholas Barton; Kirkpatrick, Mark (American Naturalist)
Many animals and plants show a correlation between the traits of the individuals in the mating pair, implying assortative mating. Given the ubiquity of assortative mating in nature, why and how it has evolved remain open questions. Here we attempt to answer these questions in those cases where the trait under assortment is the same in males and females. We consider the most favorable scenario for assortment to evolve, where the same trait is under assortment and viability selection. We find conditions for assortment to evolve using a multilocus formalism in a haploid population. Our results show how epistasis in fitness between the loci that control the focal trait is crucial for assortment to evolve. We then assume specific forms of assortment in haploids and diploids and study the limiting cases of selective and nonselective mating. We find that selection for increased assortment is weak and that where increased assortment is costly, it does not invade.

The effect of a barrier to gene flow on patterns of geographic variation - Nicholas Barton (Genetical Research)
Explicit formulae are given for the effects of a barrier to gene flow on random fluctuations in allele frequency; these formulae can also be seen as generating functions for the distribution of coalescence times. The formulae are derived using a continuous diffusion approximation, which is accurate over all but very small spatial scales. The continuous approximation is confirmed by comparison with the exact solution to the stepping stone model. In both one and two spatial dimensions, the variance of fluctuations in allele frequencies increases near the barrier; when the barrier is very strong, the variance doubles. However, the effect on fluctuations close to the barrier is much greater when the population is spread over two spatial dimensions than when it occupies a linear, one-dimensional habitat: barriers of strength comparable with the dispersal range (B≈σ) can have an appreciable effect in two dimensions, whereas only barriers with strength comparable with the characteristic scale (B\! ≈\! L \equals σ \sol \sqrt {2 μ}\hskip2) are significant in one dimension (μ is the rate of mutation or long-range dispersal). Thus, in a two-dimensional population, barriers to gene flow can be detected through their effect on the spatial pattern of genetic marker alleles.

Bayes optimal DDoS mitigation by adaptive history-based IP filtering - Goldstein,Markus; Christoph Lampert; Reif,Matthias; Stahl,Armin; Breuel,Thomas M
Distributed Denial of Service (DDoS) attacks are today the most destabilizing factor in the global internet and there is a strong need for sophisticated solutions. We introduce a formal statistical framework and derive a Bayes optimal packet classifier from it. Our proposed practical algorithm "Adaptive History-Based IP Filtering" (AHIF) mitigates DDoS attacks near the victim and outperforms existing methods by at least 32% in terms of collateral damage. Furthermore, it adjusts to the strength of an ongoing attack and ensures availability of the attacked server. In contrast to other adaptive solutions, firewall rulesets used to resist an attack can be precalculated before an attack takes place. This ensures an immediate response in a DDoS emergency. For evaluation, simulated DDoS attacks and two real-world user traffic datasets are used.